Chemical Composition of Cuticle and Barrier Properties to Transpiration in the Fruit of Clausena lansium (Lour.) Skeels - Huang, Hua; Wang, Ling; Qiu, Diyang; Lu, Yusheng (Frontiers in Plant Science, 2022)
The plant cuticle as lipid membrane covering on aerial plant surfaces functions primarily to against uncontrolled water loss. Herein, the chemical compositions of cuticle and the transpiration of wampee fruit (Clausena lansium (Lour.) Skeels) at green, turning and yellow stages in cultivar of “Jixin” (JX) and “Tianhuangpi” (THP) were comprehensively conducted. The coverage of waxes and cutin monomers per unit of fruit surface at green stage was lower in JX than in THP, and increased gradually during development. Cutin monomers accumulated ranging from 22.5 μg cm-2 (green) to 52.5 μg cm-2 (turning) in JX, and increased from 36.5 μg cm-2 (green) to 81.7 μg cm-2 (yellow) in THP. Total waxes ranged between 6.0 μg cm-2 (green) and 11.1 μg cm-2 (turning) in JX, while increased from 7.4 μg cm-2 (green) to 16.7 μg cm-2 (yellow) in THP. Cutin monomers were dominated by ω,mid-dihydroxy fatty acids (over 40 %), followed by multiple monomers of α,ω-dicarboxylic acids with or without added groups, fatty acids without or with ω- or midchain hydroxy or mid-epoxy groups, primary alcohols and phenolics. The very-long-chain (VLC) aliphatic pattern of cuticular waxes were prominently comprised of n-alkanes (ranged between 21. 4 % and 39.3 % of total wax), fatty acids, primary alcohols, and aldehydes. The cyclic waxes were dominated by triterpenoids (varied between 23.9 % and 51.2 %), sterols and phenolics. Water loss of wampee fruit exhibited linear changes over time, indicating an overall mono-functional barrier to transpiration. Permeance for water in wampee fruit was higher at green stage than at yellow stage in both JX and THP, which showed negative correlation with the changes of VLC n-alkanes. The results presented the cuticular chemicals including cutin monomers and waxes in wampee fruit, and further indicated the potential contribution of cuticular chemical compositions to the physiological functions in fruit.